Cartografando a escolarização na escola comum: pistas em narrativas que compõem o cenário da inclusão escolar - Ribeiro, Lorrayne Hewellen Cristino (2021)
The study aimed to map schooling in the common school from clues produced in the teacher training course “Policies and Practices of Special Education in an Inclusive Perspective” and in the narratives of students with disabilities from public elementary schools in the municipal network of Cariacica, ES, Brazil. Cartography was chosen as a possible way to understand reality, as a method used to monitor movements and understand processes. The study relied on the theoretical-epistemological contribution of Boaventura de Sousa Santos, adopting the concept of work of translation as a supporting pillar of analysis. It is a qualitative research. In the teacher training course, the narratives were produced by special education teachers and pedagogues. The monitoring and recording of the training moment was carried out via field journal from July to September 2019. In the schools, the narratives were produced by a student with visual impairment, a student with hearing impairment and a student with physical disability, enrolled in the final years of elementary school. As research instruments, participant observation, field journal and open interview (life history interviewing) were used. This movement took place between October and December 2019. The phenomenon of schooling in the ordinary school was contemplated through the lenses of small and large scale. As a result, the investigation points at teacher education, assumed as a tool for the elaboration of future/possible guidelines for special education, as an action coordinated by the sector of this school modality. The clues located on a small scale seem to point to a context in which the social right to Education is the structuring pillar. The involvement of everyone for school inclusion is evoked for the appropriation of the common school curriculum, an evaluation of plural and a specialized educational service of pedagogical nature in the common school, which moves away from the clinical-therapeutic bias. In the case of clues located on a large scale, the contact areas “about me”, “stigma”, “school” and “friendships” stand out, showing that students with disabilities are not a homogeneous group, but identities in progress, the presence of stigmatization processes in life and schooling trajectories, which is posed as a possibility and as a contradiction in their ongoing processes of school inclusion, as well as the importance of building friendships in these lived stories. The study points out the need of creating intelligibility between the narratives produced, of building criticisms and propositions that cooperate with the development of future/possible guidelines for special education in the municipal education network of Cariacica, ES, Brazil.